Measurement of CPOE end-user satisfaction among ICU physicians and nurses - Hoonakker, P.L.T.; Carayon, P.; Walker, J.M. (Applied Clinical Informatics, 2010)
Background: Implementation of Computerized Provider Order Entry (CPOE) can fail or meet high levels of user resistance for a variety of reasons, including lack of attention to users’ needs and the significant workflow changes induced and required by CPOE. End-user satisfaction is a critical factor in IT implementation.Objective: The goal of this study was to identify criteria to select a valid and reliable questionnaire to measure end-user satisfaction with CPOE.Methods: We developed seven criteria that can be used to select valid and reliable questionnaires. We applied the selection criteria to existing end-user satisfaction questionnaires.Results: Most of the questionnaires used to measure end-user satisfaction have been tested for reliability and validity and most of the questionnaires have reasonably reliability and some sort of validity. However, only one questionnaire, the Physician Order Entry User Satisfaction and Usage Survey (POESUS) met most of the other criteria we developed to select a questionnaire to evaluate CPOE implementation. We used the POESUS in our study and compared the results with other studies. Results show that users are moderately satisfied with CPOE.Conclusion: Using the seven criteria we developed, it is possible to select reliable and valid questionnaires. We hope that in the future this will lead to an increasing number of studies using the same questionnaires. That will improve the possibilities for comparing the results of one study to another (benchmarking).
Keywords: Computerized provider order entry (CPOE); questionnaire; evaluation; end user satisfaction; technology acceptance